Analysis of the Influence of Food Availability, Access, and Utilization on Food Security in South Minahasa Regency - Rine Kaunang; Melissa L. G. Tarore; Jenny Baroleh (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to (1) identify variables related to food availability, access, absorption, and security in South Minahasa Regency; and (2) determine the effect of food availability, access, and absorption on food security in South Minahasa Regency. The population in this study was all subdistricts in South Minahasa Regency, namely 17 subdistricts. The analysis method in this study used two approaches, namely descriptive analysis and intrinsic analysis. The descriptive analysis used in this study is presented in tables and graphs, while the inferential analysis in this study uses SEM-PLS analysis. Data processing in this study uses the Smart-PLS 4.0 application. Food security will be achieved if the three main dimensions of food security, namely: (i) availability; (ii) accessibility; and (iii) affordability by an individual (family) can be fulfilled. However, this study found that food availability does not affect food security, food access does not affect food security, and food absorption affects food security in South Minahasa Regency